1996
DOI: 10.1159/000239440
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Azithromycin on the Biofilm Formation of <i>Pseudomonas aeruginosa</i> in vitro

Abstract: The influence of azithromycin on biofilm formation by Pseudomonas aeruginosa, a cause of refractory chronic respiratory tract infection, was investigated. Alginic acid produced by a mucoid strain of P. aeruginosa was quantified by high-performance liquid chromatography from colonies growing on an agar medium. Polysaccharides in the biofilm formed on silicon chips by a nonmucoid strain were determined by a tryptophan reaction. The effect of azithromycin was examined at concentrations below the minimum inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 12 publications
4
99
1
2
Order By: Relevance
“…Our group and others have shown that azithromycin treatment can reverse the decline in lung function in some patients with BOS [32][33][34][35]. Azithromycin does not have any significant anti-pseudomonal activity but has been shown to exhibit extensive inhibition of the quorum-sensing systems, diminished virulence factor production and impairment of the oxidative stress response [36][37][38]. However, recent data suggest that although azithromycin exhibits activity against P. aeruginosa biofilms, resistant mutants are readily selected, and tailored anti-pseudomonal therapies may be required to eradicate infection in patients receiving azithromycin treatment [39].…”
Section: Cytokeratin-19mentioning
confidence: 95%
“…Our group and others have shown that azithromycin treatment can reverse the decline in lung function in some patients with BOS [32][33][34][35]. Azithromycin does not have any significant anti-pseudomonal activity but has been shown to exhibit extensive inhibition of the quorum-sensing systems, diminished virulence factor production and impairment of the oxidative stress response [36][37][38]. However, recent data suggest that although azithromycin exhibits activity against P. aeruginosa biofilms, resistant mutants are readily selected, and tailored anti-pseudomonal therapies may be required to eradicate infection in patients receiving azithromycin treatment [39].…”
Section: Cytokeratin-19mentioning
confidence: 95%
“…In addition, macrolides may have more wide ranging effects on the innate immune system, modulating neutrophil function, reducing the presentation of adhesion molecules and altering expression of nitric oxide synthases [15][16][17]. Finally, macrolides may have more mechanistic effects, reducing airway mucus production and altering the biofilm phenotype of P. aeruginosa [18,19].…”
Section: Early Reports Of Macrolides For Cystic Fibrosismentioning
confidence: 99%
“…These results show that deleting sinR may not affect macrolide resistance of the cell but may contribute to the resistance of biofilms to macrolides. SubMIC levels of AZM inhibit biofilm formation by Pseudomonas aeruginosa (Ichimiya et al, 1996), Haemophilus influenzae (Starner et al, 2008) and P. gingivalis (Maezono et al, 2011). Furthermore, P. gingivalis biofilm formation, determined using a static Fig.…”
Section: Discussionmentioning
confidence: 99%